Identifying Customer Segmentation and Persona of Online Transportation Companies in Jabodetabek Using K-Means Clustering Analysis for a More Effective Marketing Strategy - E. N. Budiyanto Hariandja,; Annisa Liestiani,; Ayu Wulandari,; Jerry Heikal, (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The demand for online transportation services in Jabodetabek has surged in recent years, driven by urbanization and the need for efficient mobility. This study aims to identify market segmentation through clustering, enabling online transportation companies to uncover detailed consumer personas and develop precise value propositions. Data was collected from 413 respondents via an online survey within the Jabodetabek area and processed with KNIME software. The analysis identified three (3) distinct user groups/clusters: The Minimum Budget Conscious Users, Value-Seeking Occasional Users, and The Established Loyalist Gentleman. Among these, The Established Loyalist Gentleman, characterized by higher income levels and frequent service usage, emerged as the ideal target segment. To attract this segment, personalized marketing strategies focusing on part of the 4Ps marketing mix are proposed. Key initiatives include Comfort and Safety Assurance, offering premium vehicles that are safe, clean, and well-maintained, along with professional drivers for a superior travel experience. Enhanced App Features include advanced safety tools like real-time trip tracking, emergency buttons, and driver identity verification to increase user trust. Ease of Booking ensures a user-friendly app interface with one-click booking and saved routes for convenience. Flexible payment methods and Special Premium Services, such as exclusive discounts for frequent or long-distance trips, further enhance loyalty. These strategies cater to the preferences of this high-value segment, fostering stronger engagement and driving long-term growth in the competitive online transportation market.